All Days 2014
DOI: 10.4043/24587-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Set-Up for Testing Cement Sheath Integrity in Arctic Wells

Abstract: Petroleum activities in the sensitive Arctic environment require increased focus on well integrity, since even small leaks can affect production and surrounding ecosystems. It is therefore of the utmost importance that the sealing ability of the annular well cement can be maintained here. This is challenging in normal locations, and difficulties are intensified when moving north. Due to the harsh topside conditions in the Arctic, the operational windows are short -and production will necessarily be turned on/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
2
22
1
Order By: Relevance
“…Similar trends, displaying that both pressure and temperature variations aggravate the casing/cement bond, were observed by Boukhelifa et al (2004) and Bois et al (2012). Detailed experimental studies of annular-cement debonding and cracking were also recently performed by Albawi et al (2014) andDe Andrade et al (2014). Both these studies show that only a few thermal cycles in the range of -20 C to 120 C cause cement debonding and cracking that are visible in computed-tomography images.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similar trends, displaying that both pressure and temperature variations aggravate the casing/cement bond, were observed by Boukhelifa et al (2004) and Bois et al (2012). Detailed experimental studies of annular-cement debonding and cracking were also recently performed by Albawi et al (2014) andDe Andrade et al (2014). Both these studies show that only a few thermal cycles in the range of -20 C to 120 C cause cement debonding and cracking that are visible in computed-tomography images.…”
Section: Introductionsupporting
confidence: 66%
“…One was at the junction between the casing and the annular-cement sheath, whereas the other was at the interface between the cement sheath and the rock. More details on the experimental setup and procedure are described in Albawi et al (2014), and similar experiments with a slightly modified setup were also performed by De Andrade et al (2014).…”
Section: Experimental Validation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the analysis of wellbore integrity under normal conditions, some scholars have carried out studies through laboratory tests, numerical simulations, and analytical modeling approaches [2][3][4][5][6]. They concluded that the wellbore trajectory, non-uniform geo-stress, cementing quality, thermal stress and fracturing operation parameters are the main factors influencing the stress variation of the casing-cement-formation system (CCFS).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends, displaying that both pressure and temperature variations aggravate the casing-cement bond, have been observed by Boukhelifa et al (2005) and Bois et al (2012). Detailed experimental studies of annular cement debonding and cracking have also recently been performed by Albawi et al (2014) andDe Andrade et al (2014). Both these studies show that only a few thermal cycles in the range Ϫ20°C to 120°C cause cement debonding and cracking that is visible in computed tomography (CT) images.…”
Section: Introductionmentioning
confidence: 99%